The Role Of Brand Communities And Community Engagement In Building Brand Trust In Social Media - Didit Aditya; Anton Agus Setyawan (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
Reviewing the history of marketing in recent years can be divided into two distinct parts, namely marketing in the pre-social media era and marketing after the emergence of social media. With the development of social media, it is easy for information to spread to remote areas, so that brand communities emerge as online communities or places for people with certain similarities or connections to meet. In addition, the brand community is a community that is not bound geographically and has a social order. The aim of this study was to analyze the relationship between brand community and community participation in building brand trust in social media. The subject of this research is PT AVO Innovation Technology (AVO), which is engaged in the cosmetics industry. This company has released several beauty products including Avoskin, Looke, and Lacoco. PT AVO Innovation Technology has a community of women. Whereas, the sample was based on the completeness of the data and the criteria determined by the researcher. The type of data used was primary data. The data collection method used a questionnaire with a sample size of 153 respondents. The results of the study indicated that a positive and significant affected on the brand community on brand trust, a positive and significant affected the participation of brand community members on product consumer trust and brand community has an effect on brand sales and brand community members affected consumer trust outside of brand community members, this can be seen by the reviews on social media.